Kontribusi Kepercayaan Diri dan Kecerdasan Emosi terhadap Komunikasi Interpersonal Siswa serta Implikasinya dalam Pelayanan Bimbingan dan Konseling - Sahputra, Dika; Syahniar, Syahniar; Marjohan, Marjohan (Universitas Negeri Padang, 2016)
This research isbackground by low ofstudents’ communication interpersonal. Self confidence and emotional intelligence were two factors assumed to affect communication interpersonal. The aims of this research were to describethe contribution of the self confidence and emotional intelligencetowards communication interpersonal. This research applied quantitative method with a descriptive correlational. The population was all thestudents of SMA Negeri 8 Padang with the total of 764 students, and the samples were 263 students that were chosen by using proportional stratified random sampling.The instrument of the research was a likert scale. Validity test result of this self confidence’s instrument was 0.503, students’ emotional intelligence was 0.430, and communication interpersonal was 0.675. Reliability test result of self confidence’s instrument was 0.819, emotional intelligence was 0.888, and communication interpersonal was 0.902. The data were analyzed by using descriptive statistics, simple and multiple regression. The research findings indicated that: (1) averagely, description of the self confidence was at high level, (2) emotional intelligence was at high level, (3)communication interpersonal was categorized at high level, (4) there was 19,6% (R=0.443, on significance 0.000) in self confidence contribution towards communication interpersonal, (5) there was 33,1% (R=0.575, significance 0.000) in emotional intelligence towards communication interpersonal, (6) there was 33,2% (R=0.576, on significance 0.000) in contribution together with self confidence and emotional intelligence towards communication interpersonal. The implication of this research can be made as a need assessment to make a program of guidance and counseling service in SMA Negeri 8 Padang.